Architectural heritage restoration of Rumah Datuk Setia via mobile augmented reality restoration - Azmin, Aida Kesuma; Kassim, Mohd Hisyammudin; Abdullah, Fadzidah; Sanusi, Aliyah Nur Zafirah (2016)
The research focuses on Mobile Augmented Reality (MAR) for architectural heritage restoration as an alternative technique to visually restore the ruined rear house of Rumah Datuk Setia, Kuala Kangsar, Perak. The research consists of the development of Virtual Heritage (VH) based on the architectural heritage information of the ruined rear house, such as spatial organization, construction, ornamentation, materials; as well as “Augmented Reality” (AR) for architectural heritage restoration via mobile devices, such as smartphone and tablet. The objective is to develop Mobile Augmented Reality Restoration (MARR) of Rumah Datuk Setia, as a showcase of architectural conservation technique, for future restoration. The research is based on action research as researchers would be directly involved in the process of producing the MARR models. The study reveals the process by integrating layers of architectural heritage information- VH and MAR as primary mediums for architectural heritage restoration. The research manifestation introduces a new technique of architectural heritage building restoration through MARR. It highlights necessary elements needed to be considered in developing the MARR, which can be applied for future architectural restorations.